Variation in the deposition of the antibodies at different anatomical sites in linear IgA disease of adults and chronic bullous disease of childhood. - Collier, P; Wojnarowska, F; Millard, P (1992)
The diagnosis of linear IgA disease of adults (LAD) and chronic bullous disease of childhood (CBDC) relies upon finding a linear band of IgA at the basement membrane zone on direct immunofluorescence. This study examines the regional variation in antigen expression in the skin of affected individuals. Direct immunofluorescence was performed on biopsies from four different sites in 17 patients with these diseases. In two patients a biopsy from the volar surface of the forearm was negative, but other sites were positive; in the remaining patients there was no variation in antibody expression with site. It is therefore recommended that, if a single diagnostic biopsy is to be taken, the volar surface of the forearm is avoided.